SEISMIC ATTRIBUTE ANALYSIS AND RESERVOIR CHARACTERIZATION OF ‘’GEORGE’’ FIELD, OFFSHORE NIGER DELTA, NIGERIA - M. T, Olowokere,; O, Abiola; J. S, Ojo (IJRDO-Journal of Applied Science, 2017)
Seismic Attribute Analysis and Reservoir Characterization of ‘George Field’ offshore Niger Delta was carried out with a view to determining the hydrocarbon potential of the area. The data set used for the study includes three dimensional seismic data and a suite of geophysical well logs from four wells A, B, C and D. In order to further confirm the presence of hydrocarbon in the identified structures, attribute analysis was carried out. The energy and the amplitude attribute extraction maps and the instantaneous frequency volume attributes maps for the reservoirs were generated. The trapping mechanism is a fault assisted closure. The amplitude, average energy and instantaneous frequency extraction maps revealed higher values around the structural highs which coincide with the locations where producing wells A, B, C and D had already been drilled thereby validating earlier interpretations that led to their drilling.